Factores asociados a malformaciones anorrectales en recién nacidos de un hospital de la amazonía peruana en el período 2015-2020 - Pinedo Pérez, Paolo (2022)
A non-experimental analytical study was carried out, with a case-control design; with the objective of determining if there are factors associated with Anorectal Malformations in newborns from a hospital in the Peruvian Amazon in the period 2015-2020. The study population consisted of 84 patients, 28 of which belonged to the Case group and 56 to the control group treated at the Neonatology service of the Regional Hospital of Loreto in the period 2015 - 2020. The data collection process was through an instrument based on a questionnaire on congenital malformations, modified for use in anorectal malformations, reviewed and validated through expert judgment by three teachers from the Faculty of Human Medicine. The data obtained were processed by the statistical software SPSS version 25. The results were: factors with moderate to very high strength of association were found among them: insufficient NPC (OR = 11,000) no consumption of folic acid in pregnancy (OR = 8,077); low birth weight (OR = 7,109), UTI in pregnancy (OR = 6920), IUGR (OR = 5667), maternal obesity during pregnancy (OR = 5392), history of cardiac malformation (OR = 4333), Oligohydramnios (OR = 4294).